Increasing awareness and reputation of Merck S.A. Portugal through employee advocacy - Sonne, Heidi Maria Tuulikki (2018)
Merck KGaA is a global Science and Technology company, focusing on the Healthcare Industry, Life Science and Performance Materials. However, Merck in Portugal is a relatively small subsidiary with a midsized office in Miraflores, employing approximately 114 employees. Merck S.A. Portugal focuses mainly on the Healthcare Market. As the company went through a major transformation in 2016, it created a need to communicate on a low cost basis and in an efficient way, using digital as its main channel. The aim of this in company project was to introduce Employee Advocacy as a solution to digital communication. Employee Advocacy is a new communications concept derived from employee social media usage and employee word of mouth. It has been noted that employee networks are wider than company’s own and employee word of mouth is more trustworthy. Before the tool could be implemented the author did a research on what motivates employees to commit to Brand Citizenship Behavior, in other words, what is the driver that makes employees want to share company content on their personal social media profiles. Findings revealed that in the case of Merck S.A. Portugal employees individual internal drive and brand knowledge are factors affecting willingness to share on social media. Based on the results a series of internal strategies were applied on- and offline.